Diversion of Union Welfare-Pension Funds of Allied Trades Council and Teamsters Local 815: hearings before the United States Senate Committee on Government Operations, Permanent Subcommittee on Investigations, Eighty-Ninth Congress, first session, on June 29, July 20-22, 1965. - United States. (U.S. G.P.O., 1965)
Investigates inadequacy of existing Federal laws regulating welfare and pension funds. Focuses on diversion of Allied Trades Council and Teamster local funds into research foundations. June 29 hearing was held in NYC.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VIII
Investigates inadequacy of existing Federal laws regulating welfare and pension funds. Focuses on diversion of Allied Trades Council and Teamster local funds into research foundations. June 29 hearing was held in NYC.
Keywords: Pensions / Law and legislation / United States.